Diagnostic Value of Narrow Band Imaging in Diagnosing Nasopharyngeal Carcinoma - Debbi Yuniserani; Bethy S. Hernowo; Agung Dinasti Permana (Althea Medical Journal, 2017)
Background: Carcinoma is the most common tumor in nasopharynx. Endoscopy is used to determine the presence of lesions suspected of malignancy. Narrow Band Imaging is an endoscopic technique that uses narrow–band spectrum as a filter to determine any mucosal vascular changes in carcinoma. Narrow Band Imaging can early detect superficial mucosal lesions that are difficult to detect with conventional endoscopy, so that diagnosing is more accurate and occurrence of unnecessary biopsies can be reduced. This study aimed to determine diagnostic value of Narrow Band Imaging in diagnosing nasopharyngeal carcinoma.Methods: This diagnostic test study was conducted at Department of Otorhinolaryngology-Head and Neck Surgery Dr. Hasan Sadikin General Hospital, Bandung from September to October 2014. Twenty four patients with clinical signs and symptoms of nasopharyngeal carcinoma that fulfilled the study criteria were assigned using consecutive sampling to examine with Narrow Band Imaging and histopathology examination. The data were then analyzed with 2x2 table to determine sensitivity, specificity, positive predictive value, negative predictive value, and accuracy.Results: In this study, the results of sensitivity, specificity, positive predictive value, negative predictive value, and accuracy in diagnosing nasopharyngeal carcinoma using Narrow Band Imaging were 93.75%, 62.5%, 83.3%, 83.3%, and 83.3%, respectively. Conclusions: Sensitivity of Narrow Band Imaging is 93.75%. [AMJ.2017;4(1):133–7] DOI: 10.15850/amj.v4n1.1034